1991
DOI: 10.1213/00000539-199110000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Acute Systemic Toxicity After the Rapid Intravenous Injection of Ropivacaine and Bupivacaine in the Conscious Dog

Abstract: Two groups of six beagle dogs received rapid intravenous (IV) injections of ropivacaine or bupivacaine on two occasions in a blinded random fashion. Initially, a dose sufficient to cause convulsions (CD) was given followed by twice the CD (2 x CD), which was administered 48 h later. The CD of bupivacaine (4.3 mg/kg) and ropivacaine (4.9 mg/kg) caused significant (P less than 0.05) increases in heart rate and mean arterial blood pressure. There was no difference between drug groups. Seizures were abolished by 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(48 citation statements)
references
References 0 publications
1
46
0
1
Order By: Relevance
“…The dosage of ropivacaine in the 0.75% RopiS group was 3 mg/kg in the present study. Feldman et al [6] reported that the intravenous dose required to induce twitching is 4.9 mg/kg for ropivacaine and 4.3 mg/kg for bupivacaine. They also observed increases in respiratory and heart rates with central nervous system toxicity after intravenous administration of bupivacaine and ropivacaine in conscious dogs.…”
Section: Discussionmentioning
confidence: 99%
“…The dosage of ropivacaine in the 0.75% RopiS group was 3 mg/kg in the present study. Feldman et al [6] reported that the intravenous dose required to induce twitching is 4.9 mg/kg for ropivacaine and 4.3 mg/kg for bupivacaine. They also observed increases in respiratory and heart rates with central nervous system toxicity after intravenous administration of bupivacaine and ropivacaine in conscious dogs.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Insulin can reverse bupivacaine-induced cardiac toxicity in animal experiments, presumably via metabolic, inotropic, and electrophysiologic mechanisms. 4,5 In the previous insulin studies, bupivacaine was infused at a rate of 0.5 mgÁkg…”
Section: Résumémentioning
confidence: 99%
“…Resuscitation after ropivacaine toxicity is more successful than bupivacaine. 7,8,9 Hence, we selected to compare these two drugs in our study.…”
Section: Variablesmentioning
confidence: 99%
“…5,6 Resuscitation after Ropivacaine toxicity is found to be more successful than Bupivacaine. 7,8,9 The improved safety profile of Ropivacaine may allow the use of higher concentrations to try and hasten the speed of onset. Ropivacaine is found to be half as potent as Bupivacaine, the potency ratio being 1.5:1 between Ropivacaine and Bupivacaine respectively.…”
mentioning
confidence: 99%